Understanding Afghan Opinion Leaders’ Viewpoints About Post-Conflict Foreign Agricultural Development: A Case Study in Herāt Province, Afghanistan - Glen C. Shinn; Richard K. Ford; Rahmat Attaie; Gary E. Briers (Journal of International Agricultural and Extension Education, 2012)
This investigation sprang from a yearlong immersion in post-conflict agricultural development environments in Herāt Province Afghanistan and from observing an array of NGO development projects. The purpose was to understand better the viewpoints of Afghan opinion leaders regarding the adoption–integration of foreign agricultural development. Objectives included (a) the identification of perceived strengths of foreign agricultural development, (b) perceived weaknesses, (c) opportunities, (d) threats, (e) anomalies, and (f)incentives and barriers. The case method fit the qualitative research design, and IRB approved the protocols. Researchers selected 15 opinion leaders (OLs) based on their knowledge, experience, and positional responsibilities. An interview guide framed 13 open-ended questions. A researcher fluent in Farsi/Pashto/English assisted with each interview. The findings from 15 interviews emerged as 11 themes. Fourteen OLs recognized agriculture and natural resources as strengths for development. Opinion leaders recognize government, infrastructure, and corruption as fundamental weaknesses. Opinion Leaders were slow to identify opportunities but generally identified opportunities to exploit labor, land, and water coupled with improving management and mechanization.They universally recognized threats related to to personal security and safety but had difficulty separating internal weaknesses from external threats. Two anomalies emerged as incongruous expectations about Afghan government and foreign NGOs. Improving market chains and increasing governmental subsidies were incentives for development. The authors conclude that indigenous knowledge is a fundamental resource and a foundation for local level decision making and sustainability. Opinion Leaders serve as channels to move the society from poverty and conflict toward security and peacebuilding. The tension between Maslow’s hierarchy of needs and Max Neef’s interrelated and interactive needs should be explored
Keywords: Extension and Advisory Services; Indigenous Knowledge; NGO; Post-Conflict Agricultural Development; Safety and Security; Sustainable Development; Value Chain Development